Influence of Dietary Black Cumin Meal (Nigella sativa L.) on the Performance and Body Measurements of Garut Sheep - Juandita, Karina Natasya; Hernaman, Iman; Alhuur, Ken Ratu Gharizah; Ramdani, Diky (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Black cumin meal has potential as feed ingredient of sheep. This study aimed to evaluate the influence of dietary black cumin meal on the performance and body measurements of Garut sheep. The study used 28 heads of male Garut sheep aged ±10 months with an average initial body weight of 20 ± 2.34 kg/head. A completely randomized design (CRD) was used to compare the influence of 4 different levels (0%, 5%, 10%, and 15%) of black cumin meal in the diet on dry matter intake (DMI, g/head/d), average daily gain (ADG, g/head/d), feed efficiency (%), body length gain (cm), chest circumference gain (cm), and height at withers gain (cm) during 70 d feeding trial using 7 replicates. The data were statistically analyzed using a One-Way Analysis of Variance and continued with Duncan new Multiple Range Test for significant results, operated by the IBM SPSS 26 program. The results showed that DMI (P<0.05), ADG (P<0.01), and feed efficiency (P<0.05) of Garut sheep were increased for a diet containing black cumin meal compared with control. Furthermore, dietary black cumin meal enhanced body length gain (P<0.05), followed by chest circumference gain, and height at withers gain (P<0.01). Dietary black cumin meal 10% is the optimum level to increase the performance and body measurements. In conclusion, dietary black cumin meal improves the performance and body measurements of Garut sheep.